Prospective Study of Clinical Outcomes From a Breast Implant Assessment Service. (15th October 2022) - Masoumi, Elnaz; Seow, Christina; Deva, Anika Preeti; Cuss, Amanda; Chow, Oliver; Davies, Matthew; Lajevardi, Sepehr; Connell, Tony; Magnusson, Mark; Beath, Kenneth; Isacson, Daniel; Deva, Anand K
Abstract: Background: Breast augmentation remains the commonest cosmetic surgical procedure worldwide, in spite of recent regulatory action. Objectives: The aim of this study was to evaluate women with breast implants attending a breast implant assessment clinic and to capture clinical and implant data in women presenting to the service. Methods: Patients were enrolled prospectively between January 2018 and December 2021. Clinical, implant, and practitioner data were recorded. Patients reported satisfaction on size, shape, and overall outcome as well as the presence or pain. Radiological evaluation, where indicated, was performed and data were included on these findings. Results: A total of 603 patients were assessed. Their mean age was 42.7 years and mean age at implantation was 29.1 years. The most common complications were capsular contracture followed by pain, waterfall deformity, and double bubble, with rupture/contracture rates increasing after the 10-year mark. The risk of double bubble was significantly lower if patients were operated on by certified practitioners (odds ratio = 0.49, P = 0.011). There was almost universally poor awareness of the risks of breast implants in patients presenting for evaluation. Conclusions: This study has shown benefit in a breast implant assessment clinic to gather information on adverse events and patient-reported outcomes following breast implant surgery. Having appropriately trained and certified practitioners perform cosmetic augmentation significantly lowers the risk of implant malposition and deformity. Any adverse event occurring within 5 years of initial surgery should be flagged as a mandatory reportable clinical indicator and trigger further investigation. Level of Evidence: 2: